PELATIHAN DAN PENERAPAN DIGITAL MARKETING DAN LABELING PADA MITRA “BAKSO KERING FROZEN IBU IPAH” DI DESA DUKUHTURI - Sarah Dien Hawa; Cintya Azmi; Eri Rahmawati; Ramadhan Wulan Yuniaris (Kanigara, 2023)
The focus of this service aims to increase sales of dried frozen meatballs which are located in the village of Dukuhturi rt01 RW 01 kec.bumiayu, kab. brebes. This service is carried out by accompanying and training a group of frozen dry meatball entrepreneurs in terms of brand management (labelling), use of digital marketing, and use of E-commers to increase business group sales during the Covid 19 pandemic. The service team provides training with material presented : 1). training inmaking marketing plans 2). training in good HR management so that motivation for performance increases 3) training and assistance in digital marketing and the use of social media and E-commerce 4) training and assistance in social media 5) training in Brand management (Labeling) so that the duplication of the brand or labeling by other parties to make it easier for consumers to recognize the product